Modeling cellular systems - Graw, Frederik; Matthäus, Franziska; Pahle, Jürgen (Springer, 2017)
This contributed volume comprises research articles and reviews on topics connected to the mathematical modeling of cellular systems. These contributions cover signaling pathways, stochastic effects, cell motility and mechanics, pattern formation processes, as well as multi-scale approaches. All authors attended the workshop on "Modeling Cellular Systems" which took place in Heidelberg in October 2014. The target audience primarily comprises researchers and experts in the field, but the book may also be beneficial for graduate students.
Includes author index.
Keywords: Cells -- Mathematical models.; elektronické knihy; electronic books